Occupational exposure to uncomfortable temperatures in two university presses of Costa Rica (UNED Research Journal, 2011)
Many industrial processes are carried out under conditions of high temperatures, creating discomfort among workers, and less frequently, a health risk, especially when heat is combined with poor ventilation and a lack of medical supervision. This problem has seldom been studied in Latin America, so this study measured the occupational exposure to overheating in workstations from the printing shops of two university publishers in a tropical city (San José, Costa Rica). We measured heat conditions in 55 workstations using a thermo-anemometer and a heat stress meter, both calibrated and certified. Workers use the workstations during the day but have several interruptions and we concluded that, even though there is a high percentage of dissatisfaction among workers regarding the temperature (50% to 80%), there is no risk of heat stress. To reduce the reported level of discomfort, we recommend that new workers be allowed an acclimation period and modification of rooms to allow more natural ventilation. Similar studies are needed in other Latin American countries, if our data are to be compared in a meaningful way.
Keywords: Occupational health; heat stress; thermal comfort; occupational exposure to high temperatures.